Analisis Penyebab Penolakan Kasus dan Faktor Penghambat Advokat Dalam Melaksanakan Profesionalitasnya - Indra Pratama; M. Yusuf Alfi Syahrin Sir; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This research is made to analyze the causes of a case or case rejected by an advocate in an effort to provide legal counsel to prospective clients and find out what are the factors that hinder an advocate in carrying out professionalism in handling a case. In this study, researchers used exploratory descriptive qualitative research methods. Exploratoryly, this research uses literature studies in its studies. This research shows that in a situation it is permissible for an advocate to reject a case or a case from a prospective client if the circumstances are in accordance with those stated in the advocate's code of ethics. In addition, there are several inhibiting factors that occur in a case so that it can hinder an advocate in carrying out his professionalism such as inadequate infrastructure facilities, time problems, and several other inhibiting factors. Keywords: Advocate; Code; Case Disclaimer